Detection of facial changes for ICU patients using KNN classifier - Muhammad Naufal, Mansor (2014)
Proceeding of The International Conference on Intelligent and Advanced Systems 2010,(ICIAS 2010) at Kuala Lumpur, Malaysian from 15 June 2010 through 17 June 2010